Pengaruh Model TSTS dan Demonstrasi Terhadap Hasil Belajar Diagram Batang Kelas V - Mita Febi Indah Sari; Suyitno; Adin Fauzi; Melinda Febriana (Madako Elementary School, 2025)
Education in Indonesia faces challenges in improving student learning outcomes, especially in mathematics. Observations at UPT SDN 2 Pakunden show that even though the learning facilities are adequate, the lecture method applied still does not actively involve students. The purpose of this study is to evaluate whether there is a significant impact of the use of the Two Stay Two Stray (TSTS) learning model combined with the demonstration method on student learning achievement in mathematics subjects. The method used is a quantitative approach with a Quasi Experiment design, Post-test Only Control Group Design. The sample consisted of 84 students in class V, who were divided into experimental and control groups. The results showed that the TSTS model with the demonstration method increased student involvement, confidence in presentation, and understanding of bar chart concepts.  This finding is based on the results of a hypothesis test with a sig (2-tailed) value of 0.004 < 0.05 which is the basis for proving the effectiveness of the application of the model in mathematics learning.  This study recommends the application of the TSTS model with a demonstration method as a more interactive and engaging learning alternative that guarantees improved mathematics learning outcomes for students.